Matemática Financeira: uma aplicação direta no cotidiano - Souza, Herbert José Cavalcanti de (2013)
In this work we study the main topics about Mathematical Finance, seeking for immediate connection with our reality. We study some subjects discussed in High School in order to provide basic tools for decision making in our daily lives. We also studied an electronic tool that helps us to solve several problems that have extensive calculations.